Validation of the need for competing inventory - Bugten, J. B.; Lugo, R. G.; Steptoe, K. (Frontiers in Psychology, 2021)
Past studies have been conducted on competitiveness and achievement orientation as two noncooperative explanations for achievement motivation and achievement behavior. But a complimentary representation of a competitive-achievement orientation has yet to be explored. This paper developed and validated the need for competing inventory (NCI), and further investigated its relations with achievement orientation, emotional assessment, self-efficacy, grit, anxiety, and flow. The results from the present study support the theoretical construct of the need for competing, in the hope that it will provide a solid foundation for a competitive-achievement orientation, which is suggested to play a significant role in competitive achievement behavior. It is anticipated that the results from the present study will open a debate for including a competitive-achievement orientation in future research with the aim for a stronger predictor for achievement behavior.